Blast waves from violent explosive activity at Yasur Volcano, Vanuatu. Issue 22 (20th November 2013) - Marchetti, E.; Ripepe, M.; Delle Donne, D.; Genco, R.; Finizola, A.; Garaebiti, E.
Abstract [1] Infrasonic and seismic waveforms were collected during violent strombolian activity at Yasur Volcano (Vanuatu). Averaging ~3000 seismic events showed stable waveforms, evidencing a low‐frequency (0.1–0.3 Hz) signal preceding ~5–6 s the explosion. Infrasonic waveforms were mostly asymmetric with a sharp compressive (5–106 Pa) onset, followed by a small long‐lasting rarefaction phase. Regardless of the pressure amplitude, the ratio between the positive and negative phases was constant. These waveform characteristics closely resembled blast waves. Infrared imagery showed an apparent cold spherical front ~20 m thick, which moved between 342 and 405 m/s before the explosive hot gas/fragments cloud. We interpret this cold front as that produced by the vapor condensation induced by the passage of the shock front. We suggest that violent strombolian activity at Yasur was driven by supersonic dynamics with gas expanding at 1.1 Mach number inside the conduit.